Risk Factors Analysis of Uygur Patients Progress to Chronic Kidney Disease after Partial Nephrectomy - Zhu, Yifei (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Despite the use of partial nephrectomy, some patients still progress to chronic kidney disease after treatment. If early interventions or surveillances were taken in patients with risk factors for chronic kidney disease, the prognosis of patients might be improved. At this time, Uygur population-based study is still unavailable. Hence, we aimed to examine new onset of chronic kidney disease in Uygur patients undergoing partial nephrectomy.Methods: Our study analyzed data of 108 patients who treated with partial nephrectomy between 2003 and 2017 at Hospital of Xinjiang Uygur Autonomous Region. Glomerular filtration rate (GFR) was estimated by the abbreviated modification in diet and renal disease study equation. Chronic kidney disease was defined as GFR <60 mL/min per 1.73 m2. We used Chi-square and Wilcoxon signed-rank test to perform Univariate analyses, and logistic multivariate regression analysis to investigate determinants of post-operative chronic kidney disease. Result: Between chronic kidney disease group and normal renal function group, the development of chronic kidney disease in patients with pre-operative GFR >60 mL/min per 1.73 m2 was related to age, pre-operative GFR, 1-week post-operative GFR, warm ischemia time, and tumor size. Final Summary: Despite the use of partial nephrectomy, some patients still progress to chronic kidney disease. Combining better surgical selection with pre-operative and post-operative chronic kidney disease surveillance may improve outcomes of patients with risk factors undergoing partial nephrectomy.